2005
DOI: 10.1002/jso.20318
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy for treatment of unexpected early‐stage gallbladder cancer

Abstract: LC for T1a and T1b gallbladder cancer needs no additional treatment, however, radical operation for T2 patients is recommended, regardless of the margin condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 20 publications
0
20
0
5
Order By: Relevance
“…Some series support simple cholecystectomy as sufficient management [10], whereas others call for radical resection in these cases [11][12][13]. Data are scant, because these lesions are uncommon.…”
Section: T1b Gbcmentioning
confidence: 99%
“…Some series support simple cholecystectomy as sufficient management [10], whereas others call for radical resection in these cases [11][12][13]. Data are scant, because these lesions are uncommon.…”
Section: T1b Gbcmentioning
confidence: 99%
“…Modern surgical series in which extended cholecystectomy was carried out, mainly from Asia, reported better survival [4][5][6][7][8][9]. In patients with tumour limited to the mucosa, in which the risk of lymph node involvement is about 2.5%, simple cholecystectomy should be enough, even when a laparoscopic approach is used [10][11][12][13][14][15]. However, the risk of lymph node involvement when the tumour invades the muscle rises to 15%, which in our opinion should require more than a simple cholecystectomy, meaning extended cholecystectomy, usually through a second surgical procedure and adjuvant radio-chemotherapy (RT-CT).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2012) observed that early diagnosis and timely radical surgery are directly correlated to the prognosis of the patients. Incidental detection of gall bladder cancer in cholecystectomy specimen do has been reported in 0.3-2% of all cholecystectomy performed for benign conditions (Lam et al, 2005;Sun et al 2005;Misra et al, 2006).…”
Section: Introductionmentioning
confidence: 99%